Penggunaan Eponim pada Penamaan Jalan Wilayah Kota Jember, Jawa Timur: Kajian Lanskap Linguistik - Fatwa, Yuniar; Firjinia Fatwa, Yuniar; Widyaruli Anggraeni, Astri; Merdeka Citraningrum, Dina (JURNAL KONFIKS, 2025)
Street naming, as a part of the linguistic landscape, serves not only as a spatial identifier but also conveys historical, cultural, and local identity values. In Jember City, many streets are named after eponyms or influential figures, yet public awareness of the historical and symbolic meanings behind these names remains low. This phenomenon is significant to study because the naming of streets reflects social and historical dynamics within society. The purpose of this research is to identify the categories of eponyms used in Jember’s street naming and to describe their contextual meanings, which include the origin of the figures, historical background, contributions, and their relation to Jember’s local culture. This study uses a descriptive qualitative approach with data collected through Google Maps observation and literature reviews from government websites, local media such as Radar Jember, village portals, Wikipedia, academic articles, and historical records. The collected data, consisting of eponymous street names, were analyzed to classify categories and interpret the historical and cultural values reflected in them. Eight categories were identified: Kings (8), Religious Figures (7), Wali Songo (3), National Heroes (14), Revolutionary Heroes (4), Educational Figures (2), Health Figures (1), and Community Leaders (2). The National Heroes category dominates, symbolizing the strengthening of nationalism, struggle, and dedication. The contextual meanings highlight respect for figures, reinforcement of local identity, religious values, and appreciation of contributions to education and health. Overall, eponym-based street naming in Jember functions as a symbolic medium connecting public space with history, moral values, and collective pride.